Investigation of the Renal Defensive Influence of Walnut Septa Extract Against Acute Renal Ischemia/Reperfusion Injury - Seda Askin; Khasiiat Iminova; Bahri Avci; Hakan Askin (Mediators of Inflammation)
Conclusion: These findings suggest that extract could be a promising therapeutic candidate for renal ischemia-reperfusion (RIR) injury. Further comprehensive and long-term studies are recommended to validate these findings.